Metode Pembelajaran Pendidikan Agama Islam Pada Anak Tunagrahita Di SLB C Muzdalifah Medan - Sormin, Darliana; Kumalasari, Intan (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2019)
This study is a qualitative research by describing the method in teaching Islamic studies in SLB C Muzdalifah Medan. Sources of data in this study are two, primary data and secondary data. The primary source is the data that was obtained directly from SLB C Muzdalifah Medan field and secondary data are books of Islamic Education and all theories of child mental retardation. Techniques of data collection by interview, observation, and documentation. Data analysis techniques are using data reduction, data display, and conclusion. Based on the results of this research, the methods used in teaching Islamic studies are lecture, demonstration, discussion, stories and exercises/ drills